Measures used to assess interventions for increasing patient involvement in Danish healthcare setting: a rapid review - Camilla Palmhøj Nielsen; Mette Terp Hoybye; Annette de Thurah; Hilary Bekker; Liv Marit Valen Schougaard; Mette Spliid Ludvigsen; Bente Skovsby Toft; Lotte Rodkjaer; Anne Bendix Andersen; Berit Nielsen; Jens Thusgård Hørlück; Lisbeth Kallestrup; et al. (BMJ Open)
Objective To identify measures used within Denmark evaluating any type of intervention designed to facilitate patient involvement in healthcare.Design Environmental scan employing rapid review methods.Data sources MEDLINE, PsycInfo and CINAHL were searched from 6–9 April 2021 from database inception up to the date of the search.Eligibility criteria Quantitative, observational and mixed methods studies with empirical data on outcomes used to assess any type of intervention aiming to increase patient involvement with their healthcare. Language limitations were Danish and English.Data extraction and synthesis Two independent reviewers extracted data from 10% of the included studies and, due to their agreement, the data from the rest were extracted by first author. Data were analysed with reference to existing categories of measuring person-centred care; findings were synthesised using narrative summaries. Adapted Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines were used to guide reporting.Results Among 3767 records, 43 studies met the inclusion criteria, including 74 different measures used to evaluate interventions aimed at increasing patient involvement within healthcare in Danish hospital and community settings. Generic measures assessed: patient engagement (n=3); supporting self-management (n=8); supporting shared decision-making (n=9); patient satisfaction and experiences of care (n=11); health-related patient-reported outcome (n=20).Conclusions Across Denmark, complex interventions designed to improve patient involvement with healthcare vary in their goals and content. Some targeting healthcare professionals, some patient health literacy and some service infrastructure. A plethora of measures assess the impact of these interventions on patient, professional and service delivery outcomes. Few measures assessed patient involvement directly, and it is unclear which proxy measures capture indicators of perceived involvement. Lack of conceptual clarity between intervention goals, the components of change and measures makes it difficult to see what types of intervention can best support change in services to ensure patients are more effectively involved in their healthcare.